UPAYA PEMBENTUKAN KELUARGA SAKINAH PADA PASANGAN YANG TIDAK MEMILIKI KETURUNAN (Jurusan Bimbingan dan Konseling Islam, 2015)
Inside answer set of problems mentioned. Researcher use method qualitative with analysis qualitative descriptive. Inside analyze eforts formation happy family at partner which no possess decline in village karang tinggil pucuk lamongan, data which in order to be paid a fee yield interview, observation and documentation which in place inside chapter presentation data and analysis data.Yield research this explain that: Factor formation happy family by father Karno with mother Ari that is pole religion, accept which in line God, accept as examination, patience be grateful to God to God about comfort; Effort compose happy family which in arraging by family father Karno with mother Ari that is become leader family which distinct, behavior which can comfortable liver partner, another appreciate between husband wife.